OCB ditinjau dari Workplace Spirituality dan Quality of Work Life - Askafi, Eka; Mahomed, Anuar Shah Bali (REVITALISASI : Jurnal Ilmu Manajemen, 2026)
The objective of this study is to examine the effect of quality of work life, workplace spirituality and organizational citizenship behavior, also testing the effect of quality of worklife, workplace spirituality. The population in this study were all Islamic teachers in East Java Indonesia using Proportionate Random Sampling. The data analysis in this study is Stuctural Equation Modelling (SEM) using software AMOS 26.0 with the result quality of work life and workplace spirituality have a significant effect on organizational citizenship behavior. These results indicate that good quality of work life and good workplace spirituality encourages teachers as organizational citizens to have a good behavior and it can encourege teachers to good performance. Organizational citizenship behavior appears as a feeling of being a member of the organization and be satisfied if it can do something more to the organization, because the organization's behavior is an act of a person resident outside obligations, do not pay attention to self-interest, does not require a job description and formal reward system, and is voluntary.